FORMULASI SEDIAAN MIKROEMULSI TRANSDERMAL PIROKSIKAM DENGAN MENGGUNAKAN VIRGIN COCONUT OIL (VCO) SEBAGAI FASE MINYAK - Yola Desnera Putri; Haruman Kartamihadrja; Lusi Fauziah (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
Piroxicam is a non-steroidal anti-inflammatory drug thus in the oral dosage of piroxicam often can irritate the stomach, thus piroxicam was made be of a transdermal microemulsion preparation. The research was conducted in the preparation of transdermal piroxicam microemulsions by used Virgin Coconut Oil (VCO) as oil phase and tween 80 as a surfactant. The formula was varied into 5 formulas with distinguished tween 80 concentrations of 40%, 45%, 50%, 55%, 60% and propylene glycol as cosurfactants with 15% concentration, and emulsion preparations without the addition of propylene glycol as cosurfactants. This study aimsed to created a stable and transparent physically microemulsion preparation and determined piroxicam the ratio of diffusion rate in piroxicam microemulsions and piroxicam emulsions. The test was performed by using Franz diffusion test by using Whatman membrane. In the microemulsion formula, the percentage of diffused piroxicam content obtained was greatest at F5 (24.35%) at 180 minutes and compared to emulsion (2,66%). The diffusion test resultsed show that the effect of addition of cosurfactant at the diffusion rate of the microemulsion preparation is compared to the emulsion preparation without the addition of cosurfactant. This cosurfactant can help surfactants to penetrate skin membranes.